2016
DOI: 10.1136/bmjopen-2016-011961
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between substance use and sexual behaviour in young people in Britain: findings from a national probability survey

Abstract: BackgroundHealth risk behaviours are prominent in late adolescence and young adulthood, yet UK population-level research examining the relationship between drug or alcohol use and sexual health and behaviour among young people is scarce, despite public health calls for an integrated approach to health improvement. Our objective was to further our understanding of the scale of and nature of any such relationship, using contemporary data from Britain's third National Survey of Sexual Attitudes and Lifestyles (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 31 publications
(34 reference statements)
7
46
0
1
Order By: Relevance
“…Studies in the United Kingdom show that the youth, particularly young boys, who engage in multiple substance use were more likely to report risky sexual behavior. 11 Although the number of the youth involved in multiple risky behaviors was small in this study, these results aligned with several studies from other countries showed that concurrent multiple risk behavior is associated with low self-efficacy and low self-esteem, as well as a general propensity toward potential risk-taking that is related to the self-regulation capacity influenced by adolescent brain development. 11 This study showed that 28% of adolescent were currently dating; this aligns with the fact that most respondents were still in high school and were very young (the average age was 16).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies in the United Kingdom show that the youth, particularly young boys, who engage in multiple substance use were more likely to report risky sexual behavior. 11 Although the number of the youth involved in multiple risky behaviors was small in this study, these results aligned with several studies from other countries showed that concurrent multiple risk behavior is associated with low self-efficacy and low self-esteem, as well as a general propensity toward potential risk-taking that is related to the self-regulation capacity influenced by adolescent brain development. 11 This study showed that 28% of adolescent were currently dating; this aligns with the fact that most respondents were still in high school and were very young (the average age was 16).…”
Section: Discussionsupporting
confidence: 88%
“…Studies in the United Kingdom (UK) and the United States (US) have found associations between substance use and risky sexual behavior among adolescents. 11 When youths participate in one risky health behavior, they tend to participate in other risky health behavior. 12 Despite the assumption of an association between smoking, alcohol, and risky sexual behavior, there is limited study targeting youth with multiple risk behavior, particularly in Central Java.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health conditions and symptoms of depression were common in this cohort; participants reporting the high-risk phenotype had increased risks of all three measures of poor mental health status, consistent with the findings from the general population [4]. Potential mechanisms for this relationship could include use of substances to cope with mental health symptoms, or risk of mental health problems secondary to substance use [5].…”
Section: Discussionsupporting
confidence: 78%
“…Our finding that a higher frequency of binge drinking (once a month or more) is associated with a higher number of sexual partners (five or more partners) is in line with previous research. Alcohol and substance use may reduce inhibitions and impair judgement in these users, which can manifest on their sexual behaviour regarding unplanned sex, having first sex with their last partner after they had only recently met or multiple partners, sexual activity in early teenage years and also on their poor sexual health outcomes [ 55 , 56 , 57 , 58 , 59 ], including chlamydial infection [ 60 ].…”
Section: Discussionmentioning
confidence: 99%